Customer perceived value in freemium business model. Case study: Spotify in Finnish and Vietnamese market - Khong, Thi Anh Thu (My University, 2019)
Freemium business model has become more popular in digital economy in practice and therefore, become a phenomenon that worth to research. There have been so far only few researches about customer perceived value in freemium business model. This research deepened the understanding of customer value perception about Premium and free versions based on value theory. In addition, put into the context of emerging market and mature market, the study aimed to find the differences of customer perceived value in different market cycle. The study confirmed the difference of perceived value of the same product in different markets. In the mature market (Finland), the Premium version of freemium service Spotify has become basic and standard, therefore, the perceived cost was only money and there was no aesthetic value found. People chose Premium mainly because of its functionally convenience rather than to imply some positive meaning about themselves through the purchasing decision. On the other hand, in the emerging market (Vietnam), Premium version was perceived as the more sophisticated luxury version. The perceived cost was not only money but also the willingness to pay for the better version of the service. Aesthetic value was found, as using Premium was perceived as transferring positive messages related to their financial status, lifestyle and music taste.
Keywords: freemium business model; customer perceived value; Spotify; Finland; Vietnam; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|